Graph-Based Report Creation Training with PHP + Chart.js - Nasution, Adnan Buyung; Hrp, Ahir Yugo Nugroho; Fauzi, Muhammad; Adhar, Deni (Jurnal Pengabdian Masyarakat Bestari, 2024)
This training aimed to enhance participants' skills in creating graph-based reports using Chart.js, a popular JavaScript library for data visualization. The training methodology involved both theoretical sessions and hands-on practice, where participants were instructed on the basic usage of Chart.js, creating various types of charts such as bar charts, line charts, and pie charts, and integrating these charts into reports. The results of the training showed a significant improvement in participants' understanding and proficiency in using Chart.js to visually present data. In conclusion, the training successfully provided tangible benefits in improving the quality and clarity of reports produced by participants, equipping them with practical tools for their daily work.